Addressing Racism, Politics and the Pivotal 2018 Midterm Point: Social Network Analysis of Black Lives Matter Twitter Discourse. (December 2022) - LaPoe, Benjamin R.; LaPoe, Victoria Leigh; Carter Olson, Candi S.; Hazarika, Bharbi; Woellert, Allyson
This study examines Twitter data collected by Netlytic building up to the 2018 midterm election date as well as one month after. We conducted a social network analysis and a semantic textual analysis of the data. Prior research on network discourse of Black Lives Matter, a social movement organically created from a hashtag on social media following the acquittal of Trayvon Martin's killer George Zimmerman, found Black victims of police brutality and systemic racism were victim blamed. This present study maps tweets, showing communication networks formed around Black Lives Matter and what the networks communicated. Through our analysis, eight distinct virtual community networks emerged.